Age-related dedifferentiation of cognitive and motor slowing: insight from the comparison of Hick–Hyman and Fitts’ laws - Sleimen-Malkoun, Rita; Temprado, Jean-Jacques; Berton, Eric (Frontiers in Aging Neuroscience, 2013)
The present study aimed to determine whether the general slowing hypothesis could be extended to the motor domain by comparing cognitive and motor age-related slowing. To achieve this objective, we compared the slopes of Hick-Hyman’s law and Fitts’ law, in young and older adults. The general hypothesis was that, due to the dedifferentiation of cognitive and motor neural resources during aging, the slopes of Hick-Hyman's law and Fitts’ law should become closer, if not similar, in older adults. Ten young adults (mean age = 26 ± 3 years) and fourteen older adults (mean age = 78 ± 7 years) participated in the experiment. They had to perform a discrete rapid-aiming task and a reaction time task. In the aiming task, five ID levels were used (from 3 to 7 bits by increments of 1.0 bit). Task difficulty was scaled via the manipulation of target distance from home position. In the reaction time task, 5 IDs were selected: 0, 1, 2, 3 and 4 bits, with incompatible S-R associations. Reaction time and movement times were recorded. Efficiency and Brinley regression functions were calculated. Age-related slowing ratios were estimated. Response times increased in both tasks in older adults. The slopes of Hick-Hyman’s law and Fitts’ law were steeper in older adults than in young participants. In young participants, the slope of Hick-Hyman’s law was smaller than that of Fitts’ law. In older adults, no difference was found. Slowing ratios observed in both tasks were equivalent. The present results extended the general slowing hypothesis to the motor domain. They suggested that, due to dedifferentiation of cognitive and motor neural resources, decrease in processing speed acts as a common cause to behavioral slowing in both cognitive and motor tasks.